Development of the Platysma Muscle and the Superficial Musculoaponeurotic System (Human Specimens at 8–17 Weeks of Development) - C. De la Cuadra-Blanco; M. D. Peces-Peña; L. O. Carvallo-de Moraes; M. E. Herrera-Lara; J. R. Mérida-Velasco (The Scientific World Journal)
There is controversy regarding the description of the different regions of the face of the superficial musculoaponeurotic system (SMAS) and its relationship with the superficial mimetic muscles. The purpose of this study is to analyze the development of the platysma muscle and the SMAS in human specimens at 8–17 weeks of development using an optical microscope. Furthermore, we propose to study the relationship of the anlage of the SMAS and the neighbouring superficial mimetic muscles. The facial musculature derives from the mesenchyme of the second arch and migrates towards the different regions of the face while forming premuscular laminae. During the 8th week of development, the cervical, infraorbital, mandibular, and temporal laminae are observed to be on the same plane. The platysma muscle derives from the cervical lamina and its mandibular extension enclosing the lower part of the parotid region and the cheek, while the SMAS derives from the upper region. During the period of development analyzed in this study, we have observed no continuity between the anlage of the SMAS and that of the superficial layer of the temporal fascia and the zygomaticus major muscle. Nor have we observed any structure similar to the SMAS in the labial region.